THE EFFECTS OF LEVERAGE, FIRM SIZE, CASH FLOW VOLATILITY, AND TAX AVOIDANCE ON CASH HOLDING IN THE 2020-2021 PANDEMIC PERIOD - Hastuti, Rini Tri; Rasyid, Ardiansyah; Ashianti, Agnes (International Journal of Application on Economics and Business, 2023)
This research aims at how the role of the leverage, firm size, cash flow volatility, and tax avoidance on cash holding in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020-2021 Manufacturing companies listed on the Stock Exchange Indonesia during 2020-2021 and is also available on the eddyelly website. The sample was selected using by 54 companies were included in the valid data when the sample was chosen using the purposive sampling technique. Multiple regression analysis is used during data processing method, using help from Ms. Excel and the Windows version of Eviews version 12 for Windows 10 and Microsoft Excel 2019. The findings of this investigation suggest that leverage has a significant negative effect on cash holding, firm size, cash flow volatility shows an insignificant negative effect on cash holding and there is empirical evidence related to this study while tax avoidance shows an insignificant positive effect on cash holding and there is no evidence empirical research. The implication of this research is the benefit of the company`s internal parties regarding the variable cash holding with independent variables and as relevant new evidence related to liquidity, substantial dependence and the use of complementary liquidity sources.